HOW GROUP DISCUSSION AND CONTEMPORARY LITERATURE INCREASE STUDENTS’ MOTIVATION IN ENGLISH LITERATURE SUBJECTS: A CASE STUDY AT 4TH SEMESTER STUDENTS OF STIKUBANK UNIVERSITY IN 2017/2018 ACADEMIC YEAR - Fransiska Marsela Hambur (Universitas Stikubank (UNISBANK) Semarang, 2018)
Foreign language teachers need to motivate their students to learn English. Literature can be a good means to achieve motivation in literature classes. There has recently been a revival of interest in literature as a practical, motivating and an effective resource available for language learning. Therefore, we can assume that literature and authentic literary materials, especially short stories can enhance students’ motivations. This study focuses on how students’ motivation can be lifted through the use of group discussion as class activities and contemporary literature as learning material. This study is a descriptive qualitative which used questionnaire as main instrument to find out how college students rate English Literature Course and how students can be motivated with certain group activities with certain learning material. The result of this study shows that students rated 82 out of 100 for English Literature Course using group discussion as class activity and contemporary literature as learning material. From this study, there is an obvious implication that college students may enjoy learning English Literature through the utilization of contemporary literature and group discussion. This study found that instead of reading short extracts presented in course books, or any classical short stories, contemporary literature were more suitable complete texts for students to become fluent and competent language users. By learning English through literature, the students’ knowledge and competence are enhanced not only through formal English lessons, but rather through informal cognitive ways, in where the students are invited to examine and analyze how human’s life are portrayed through vocabularies, grammatical structures, and sociocultural dimensions of language.